Teknik-teknik yang Fungsional dalam Memadukan Pembelajaran Keterampilan Berbahasa Lisan Bahasa Indonesia di Tingkat SLTP - Emidar Emidar (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2008)
The discussion of this paper is about simple and practical techniques of in integrating the teaching of Indonesian spoken language skills (listening and speaking) at Junior High School. The focus of teaching is developing speaking skill. The techniques are description technique, comprehension question, continuing story, series of story, retelling the story, guessing pictured story, giving clues and role playing. Keywords: speaking skill, listening skill, technique, integrated, practice, teaching learning process, Indonesian lesson